ALS is imprinted in the chromatin accessibility of blood cells - Kühlwein, Julia K.; Ruf, Wolfgang P.; Kandler, Katharina; Witzel, Simon; Lang, Christina; Mulaw, Medhanie A.; Ekici, Arif B.; Weishaupt, Jochen H.; Ludolph, Albert C.; Grozdanov, Veselin; Danzer, Karin M. (Cellular and molecular life sciences, 2023)
Amyotrophic Lateral Sclerosis (ALS) is a complex and incurable neurodegenerative disorder in which genetic and epigenetic factors contribute to the pathogenesis of all forms of ALS. The interplay of genetic predisposition and environmental footprints generates epigenetic signatures in the cells of affected tissues, which then alter transcriptional programs. Epigenetic modifications that arise from genetic predisposition and systemic environmental footprints should in theory be detectable not only in affected CNS tissue but also in the periphery. Here, we identify an ALS-associated epigenetic signature (‘epiChromALS’) by chromatin accessibility analysis of blood cells of ALS patients. In contrast to the blood transcriptome signature, epiChromALS includes also genes that are not expressed in blood cells; it is enriched in CNS neuronal pathways and it is present in the ALS motor cortex. By combining simultaneous ATAC-seq and RNA-seq with single-cell sequencing in PBMCs and motor cortex from ALS patients, we demonstrate that epigenetic changes associated with the neurodegenerative disease can be found in the periphery, thus strongly suggesting a mechanistic link between the epigenetic regulation and disease pathogenesis.
Gesehen am 17.09.2024